2009
DOI: 10.1007/s11695-009-9866-y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Outcome of Gastric Bypass Surgery Utilizing Personality Scale Elevations, Psychosocial Factors, and Diagnostic Group Membership

Abstract: Results support the K scale of the MMPI-2 as a significant predictor of postsurgical outcome; MCMI scores on the schizoid, schizotypal, and compulsive scales appeared to be better overall predictors of outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Thus, our results support the findings of the literature that associate bariatric surgery with the rapid improvement of medical comorbidities. 6,[28][29][30] Another important aspect of our data is that the patients here assessed had a peculiar characteristic: with a focus on the continued empowerment of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results support the findings of the literature that associate bariatric surgery with the rapid improvement of medical comorbidities. 6,[28][29][30] Another important aspect of our data is that the patients here assessed had a peculiar characteristic: with a focus on the continued empowerment of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the elevations were not above the clinical cut-off for these scales, the clinical significance of this finding is unclear. A recent study using both the MMPI-2 and the Millon Multiphasic Clinical Inventory (MCMI-III) found that the K-scale from the MMPI-2 and the Schizoid, Schizotypal, and Compulsive scales from the MCMI-III predicted weight loss, but differentially at various post-operative time points (Belanger, Wechsler, Nademin, & Virden, III, 2010). Additionally, the sample used in this study was inclusive of patients who had been approved without reservation and patients who had received psychological/psychiatric treatment presurgically or concurrent with the procedure, making it difficult to draw conclusions.…”
Section: What Is Known -Paradoxical Resultsmentioning
confidence: 99%
“…In a cluster analytic approach to determine psychological profiles in 153 candidates for vertical banded gastroplasty, 3 distinct patterns were found that were comprised of combinations of high to low functioning, but these occurred across 7 domains (personality, coping, eating behavior, locus of control, body attitude, social functioning, and health-related quality of life) (van Hout, van Oudheusden, Krasuska, & van Heck, 2006). Generally, the research in the area of personality profiles has pointed to the heterogeneity of presurgical candidates and an inability to uniformly predict outcomes (Belanger 2010).…”
Section: What Is Known -Paradoxical Resultsmentioning
confidence: 99%
“…Belanger et al 37 MMPI-2 MCM-III BMI MMPI-2: ↑K was predictive of less BMI reduction at all assessment times. MCM-II: in a 1-factor predictive model, ↓C was predictive of greater BMI reduction (T1).…”
Section: General Description Of Articles Assessedmentioning
confidence: 97%
“…According to the same findings, a compulsive personality profile was also negatively associated with weight reduction. 37 Although the authors did not describe what they considered maladaptive eating behavior to comprise (it is unclear whether they are referring, for example, to non-compliance with nutritional guidance, to psychopathological eating behavior, bulimia, etc.) and the instrument employed to assess it is unpublished, it nevertheless appears that patients who exhibited dysfunctions in the externalizing domain were already exhibiting unhealthy eating behavior at 3 months and were more likely not to attend consultations 12 months after the procedure.…”
Section: General Description Of Articles Assessedmentioning
confidence: 99%